KIAT-KIAT UNTUK GURU AGAR SISWA AKTIF TERLIBAT AKTIF DI DALAM KELAS BAHASA - Mualimin, Mualimin; Kistanto, Nurdien Harry (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
Students in language classes are sometimes reluctant to be active. This condition can be a problem for teachers because in learning languages students are supposed to be actively involved and they even enjoy the activities. This paper aims at exploring some teaching and learning strategies and enjoyable activities that teachers may use in their classes so that students in the class are provoked to be involved in and enjoy the activities in their classes. To discuss this matter the writer has collected some references from books and journals on the matter. The discussion will cover teaching methods and strategic activities or techniques that teachers may find them useful to cater for such problems. By considering such methods and startegies it is hoped that the students of language classes will have enjoyable activities in their class and they will have a better achievement in their learning processes. Key words: teaching and learning strategies, enjoyable activities, language classes